The evolving roles of alarin in physiological and disease conditions, and its future potential clinical implications - Abebe, Endeshaw Chekol; Mengstie, Misganaw Asmamaw; Seid, Mohammed Abdu; Malik, Tabarak; Dejenie, Tadesse Asmamaw (Frontiers in Endocrinology, 2022)
Alarin is a member of the galanin family of neuropeptides that is widely expressed in the central nervous system and peripheral tissues in humans and rodents. It was initially isolated fifteen years ago in ganglionic cells of human neuroblastoma. Subsequently, it was demonstrated to be broadly distributed in the blood vessels, skin, eyes, peripheral and central nervous systems, thymus, gastrointestinal tract, and endocrine organs of different species. Alarin is a 25 amino acid neuropeptide derived from the alternative splicing of the GALP gene, missing exon 3. It is found to be involved in several physiological functions that include feeding behavior, energy homeostasis, glucose homeostasis, body temperature, and reproduction. It has also vasoactive, anti-inflammatory, anti-edema, and antimicrobial activities. However, the physiological effects of alarin have not been fully elucidated and the receptors that mediate these effects are not currently known. Unearthing the novel biological effects of alarin and its unidentified receptors will therefore be a task in future biomedical research. In addition, alarin is involved in various disease conditions, such as metabolic syndrome, obesity, insulin resistance, type 2 diabetes, diabetic retinopathy, hypertension, cardiac fibrosis, polycystic ovarian syndrome, and depression. Thus, alarin may serve as a promising tool for future pharmacological treatment and diagnosis. But further research is awaited to confirm whether alarin has a protective or pathological role in these diseases. This article provides a comprehensive review on the evolving implications of alarin in a variety of physiological and disease conditions. It also highlights the distribution, structure, biosynthesis, and future perspectives of alarin.